2018
DOI: 10.1039/c7cc07692d
|View full text |Cite
|
Sign up to set email alerts
|

‘AIE + ESIPT’ assisted photorelease: fluorescent organic nanoparticles for dual anticancer drug delivery with real-time monitoring ability

Abstract: 'Aggregation Induced Emission + Excited State Intramolecular Proton Transfer (AIE + ESIPT)'-assisted photorelease of an anticancer drug by a p-hydroxyphenacyl (pHP) phototrigger with real-time monitoring has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Certain 2‐naphthol tethered Schiff bases show fluorescence emissions due to excited state intramolecular proton‐transfer and the intensity of emission in each case was enhanced upon addition of water. It is also suggested that ESIPT and AIE took place in those hydroxy‐aromatic imines and the emissions were dependent on the concentration of water . Based on these one may suggest that the emission occurring at the 446 nm of 2‐hydroxynaphthaldoxime upon addition of water is due to a combine effect of ESIPT and AIE.…”
Section: Resultsmentioning
confidence: 97%
“…Certain 2‐naphthol tethered Schiff bases show fluorescence emissions due to excited state intramolecular proton‐transfer and the intensity of emission in each case was enhanced upon addition of water. It is also suggested that ESIPT and AIE took place in those hydroxy‐aromatic imines and the emissions were dependent on the concentration of water . Based on these one may suggest that the emission occurring at the 446 nm of 2‐hydroxynaphthaldoxime upon addition of water is due to a combine effect of ESIPT and AIE.…”
Section: Resultsmentioning
confidence: 97%
“…74 It is also the basis for revealing the complex relationship between dietary exposure and chronic diseases with metabolic phenotypic changes. 75 The emergence of nutritional metabolomics has two main objectives: (1) to determine the effects of dietary compounds on host metabolism within a certain period of time; (2) to determine the biomarkers of dietary intake or phytochemical dosedependent metabolites. 76,77 The application of metabolomics in nutrition research can generally be divided into four main elds: identication of dietary biomarkers, identication of dietary-related diseases and disease biomarkers, application of nutrition as a tool to identify molecular mechanisms in dietary intervention research, and precision nutrition.…”
Section: Metabolomics Analysis For Nutrition Sciencementioning
confidence: 99%
“…The combination of AIE with ESIPT enables probes to have excellent photophysical properties, such as large Stokes shifts and low inner‐filter effects . By virtue of this, a photoresponsive drug delivery system ( 28 , Figure ) exhibiting both AIE and ESIPT phenomena was developed . Two different drugs could be conjugated on the 28 by chemical reaction.…”
Section: Strategies To Realize Accurate Detection Using Aie Probesmentioning
confidence: 99%
“…90,91 By virtue of this, a photoresponsive drug delivery system (28, Figure 2) exhibiting both AIE and ESIPT phenomena was developed. 92 Two different drugs could be conjugated on the 28 by chemical reaction. Ascribed to ESIPT, two emission maxima, an enol form and a keto form, were observed at 470 and 560 nm, respectively.…”
Section: Combination With Other Photophysical Processesmentioning
confidence: 99%